Daiana Gârdan, Între lumi. Romanul românesc în sistemul literar modern, Casa Cărții de Știință, Cluj-Napoca, 2023, 259 p. - BRICI, Alexandra (Studia Universitatis Babeș-Bolyai Philologia, 2024)
Daiana Gârdan’s 2023 volume Între lumi. Romanul românesc în sistemul literar modern is a methodologically heteroclite reappraisal of the Romanian novel between 1845 and 1939, with the focus on the first four decades of the twentieth century, prompted by the sustained relevance of the novels published in this period in the Romanian literary canon. The volume has a macroscopical approach, informed by the instruments subsumed under Moretti’s distant reading paradigm and the most recent frameworks within World Literature scholarship. In this sense, the author reveals the gap between what has canonically been described in literary scholarship as the two poles of power in the literary field at the beginning of the twentieth century, the “modernists” and the “traditionalists”, and their various forms of rhetoric with regards to the novel on the one side, and literary production brought to light by Gârdan’s distant readings on the other. As the author demonstrates, the gap between the clear-cut and often unequivocal appraisals of the Romanian novel that literary historiography and contemporary literary scholarship are tributary to and the reality of literary production is seldom made visible through traditional heuristic instruments. Her analysis is focused on the reevaluation of the two most prominent genres of the period, the rural novel and the urban novel, to which she adds a third category, the interstitial novel.